The identification of physiological traits in wheat confering passive resistance to Fusarium head blight - Jones, Stephen P. T. (2015)
Fusarium head blight (FHB) is a devastating fungal disease of wheat and other small grain cereals worldwide caused by a complex of toxigenic Fusarium spp. and non-toxigenic Microdochium spp. Infection leads to a reduction of grain yield, loss of grain quality and the production of harmful mycotoxins. Control methods for FHB include both cultural and chemical strategies, however the development of cultivars with improved FHB resistance is considered as the most sustainable method for controlling the impact of this disease.